2006
DOI: 10.1016/j.newast.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

On the use of Ajisai and Jason-1 satellites for tests of general relativity

Abstract: In this paper we analyze in detail some aspects of the proposed use of Ajisai and Jason-1, together with the LAGEOS satellites, to measure the general relativistic Lense-Thirring effect in the gravitational field of the Earth. A linear combination of the nodes of such satellites is the proposed observable. The systematic error due to the mismodelling in the uncancelled even zonal harmonics would be ∼ 1% according to the latest present-day CHAMP/GRACE-based Earth gravity models. In regard to the non-gravitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…combinations and the CHAMP/GRACE models Iorio [163,164] studied the impact of the new CHAMP/GRACE-based Earth gravity models on alternative combinations including the nodes of Ajisai and Jason-1 as well able to remove, in principle,…”
Section: Alternativementioning
confidence: 99%
See 1 more Smart Citation
“…combinations and the CHAMP/GRACE models Iorio [163,164] studied the impact of the new CHAMP/GRACE-based Earth gravity models on alternative combinations including the nodes of Ajisai and Jason-1 as well able to remove, in principle,…”
Section: Alternativementioning
confidence: 99%
“…To date, his suggestion has not yet been practically implemented by anyone. A SAV calculation [164] extended to = 40 with EIGEN-CG03C [134], EIGEN-CG01C [135], EIGEN-GRACE02S [125] and GGM02S [136] provided an upper bound of 1 0 − 2 6% of the systematic bias due to the even zonals. Iorio [164] concluded that a test with a total accuracy of 4 − 5% over at least 3 years would be possible.…”
Section: Alternativementioning
confidence: 99%
“…The total uncertainty reached is still matter of debate [78,79,80,81,82,83,84] because of the lingering uncertainties in the Earth's multipoles and in how to evaluate their biasing impact; it may be as large as ≈ 20−30% according to conservative evaluations [78,81,82,83,84], while more optimistic views [73,74,76] point towards 10 − 15%. Several authors [85,86,87,88,89] explored the possibility of using other currently orbiting SLR geodetic satellites in addition to LAGEOS and LAGEOS II. A new SLR geodetic satellite, named LARES, should be launched by the Italian Space Agency (ASI) in 2010 to improve the present-day accuracy of the Lense-Thirring tests by combining its node with those of the existing LAGEOS and LAGEOS II [91].…”
Section: Experimental/observational Overviewmentioning
confidence: 99%